Growth spillover: a spatial dynamic panel data and spatial cross section data approaches in selected Asian countries - Sahar Amidi; Ali Fagheh Majidi; Bakhtiar Javaheri (Future Business Journal, 2020)
Abstract One of the most fundamental issues worldwide is the economic interdependence of countries which affects their economic growth. Some new growth theorists such as Mankiw et al., Islam, Ertur and Koch, Lee, Yu and Yu Ho et al. consider geographical proximity and trade as spatial variables. This study aims to investigate the spatial effects of geographical distance on economic growth using the spatial dynamic panel data model and the spatial cross section data model for the period 1992–2016 in selected Asian countries. The findings demonstrate that the effect of spatial spillover or spatial dependency is one of the main causes of economic growth spillovers. In the spatial dynamic panel data model, log of gross domestic product (GDP), gross fixed capital formation and growth rate of labor force had negative, positive and negative impacts on economic growth, respectively. In the spatial cross-sectional data models including human capital, log of GDP, gross fixed capital formation and growth rate of labor force had negative impacts on economic growth, while in a model without human capital log of GDP, gross fixed capital formation and growth rate of labor force, respectively, had positive and negative effects on economic growth.